THE OPTIMATION OF FERMENTATION FOR METABOLITE PRODUCTION BY SYMBIONT Penicillium nalgiovense FROM THE SPONGE Gelliodes fibulata - Rusmalina, Siska; Mahfur, Mahfur; Ermawati, Nur; Maliah, Nabilatun; Ananda, Luthfiah; Bintang Pratama, Kevin; Evi Ulfiani , Riska; Abdul Aziz, Danang; Husain, Khafidz; Ilma Faza, Febi; Hidayatullah, Adib (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2025)
The fungi are sponge symbionts. The fungus Penicillium nalgiovense acc MK087096 is a symbiont of the sponge Gelliodes fibulata. This symbiont has antibacterial activity, which supports the development of sponge-based drugs that are as effective as antibiotics. However, the primary challenge in developing marine resource-based medicine is the availability and sustainability of sponge raw materials. Fermentation biotechnology using sponge symbiont fumgi is an effective solution to address these challenges, as it allows the production of bioactive secondary metabolite compounds in large quantities, which can be used as raw materials for pharmaceutical preparation. The aim of this study was to determine the optimal medium and fermentation duration for producing secondary metabolites with antibiotic properties from the symbiotic fungus Penicillium nalgiovense, isolated from the sponge Gelliodes fibulata. This study was conducted naturally. The symbiotic fungus from the sponge Gelliodes fibulata was cultivated to facilitate growth. Fermentation was conducted with variations in secondary metabolite harvesting times of 2, 4, 6, 8, 10, and 12 days. Secondary metabolites were obstained using liquid-liquid extraction with ethyl acetate. The optimal medium and fermentation time were determined based on the yield percentage for each medium across the six time variations. The fermentation biotechnology of the symbiotic fungus Penicillium nalgiovense acc MK087096 from the spone Gelliodes fibulata was carried out on SDB, PDB, also coconut flake-enriched PDB media. The results showed the growth of the fungus and the production of bioactive secondary metabolites with antibiotic properties ...